Social evil threatens the integral development of the human person and of the human society - Migles, Silvija (Array, 2018)
This paper discusses social evil as one type of various forms of evil. That is, the Social Doctrine of the Catholic Church offers much scope for theological reflection on evil as a social phenomenon. It provides a socio-ethical perspective within which we can reflect on the reality of evil and its manifestations in the human society. The first part discusses the phenomenon of social evil and a plausible description of its essence in the context of deprivation and threats it poses to the integral human development in society. The second part points out the specific forms of social evil in the present day that threaten human dignity and prevent »full development of the whole man and of all men« (Sollicitudo rei socialis, no. 38; Populorum progressio, no. 42). Certain forms of social evil are increasingly multiplying and becoming a serious obstacle to the integral development of the human person and of the human society. Finally, the question of human freedom arises that reaches its full realization in the choice of good, which confirms the quality of existence. As true human existence cannot be thought of without its spiritual dimension that opens towards the Absolut, the path towards the full development of the whole person, of each individual and of the human society depends on the urgent need for value options.